Novel synthesis of hydroxyvinylethyl xylan using 4-vinyl-1, 3-dioxolan-2-one. Issue 37 (14th September 2016) - Akil, Youssef; Lehnen, Ralph; Saake, Bodo
Graphical abstract: Highlights: Vinyl groups were introduced into xylan by a reaction of vinyl ethylene carbonate. The substitution can be controlled by adjusting reaction time and temperature. The conversion of xylan hydroxyl groups is preferred over homopolymerization. Abstract: A novel synthesis for the incorporation of vinyl groups into the bio-polymer xylan is presented. For derivatization the cyclic organic carbonate 4-vinyl-1, 3-dioxolan-2-one was used in DMSO under alkaline conditions. As a result xylans containing vinyl functionalities are obtained. This is increasing the reactivity, for example for radical induced reactions. Derivatization was carried out at different temperatures and reaction times. Products were characterized regarding their degree of substitution, molar substitution and tendencies for homopolymerization by 13 C NMR-, HSQC-NMR-, and FTIR-spectroscopy.